2011
DOI: 10.2174/1874285801105010119
|View full text |Cite
|
Sign up to set email alerts
|

Farnesol, a Fungal Quorum-Sensing Molecule Triggers Candida Albicans Morphological Changes by Downregulating the Expression of Different Secreted Aspartyl Proteinase Genes

Abstract: The aim of this study was to determine the effect of exogenous farnesol in yeast-to-hyphae morphogenesis, and Saps (2, 4, 5 and 6) mRNA expressions by a Candida strain that does not produce endogenous farnesol. C. albicans was cultured in the absence and presence of farnesol at various concentrations (10, 100, and 300 µM), in proteinase induction medium, and then used to determine yeast-to- hyphae changes, Candida ultrastructure and to determine Saps 2, 4, 5 and 6 expressions using q-TR-PCR and ELISA (for Sap2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 48 publications
1
28
0
Order By: Relevance
“…In addition, Cope (1980) reported that fungistatic and fungicidal doses of miconazole interacted directly with the cellular components of C. albicans and resulted in an increase in the intracellular K + . Furthermore, farnesol modulated the morphogenesis of C. albicans through a downregulation of Saps 2, 4, 5, and 6 expressions (Décanis et al, 2011). However, Hultenby et al (2014) reported that treatment of C. albicans with a mixture of propylene glycol, lactic acid and urea resulted in certain ultrastructural changes but without a specific mode of action.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Cope (1980) reported that fungistatic and fungicidal doses of miconazole interacted directly with the cellular components of C. albicans and resulted in an increase in the intracellular K + . Furthermore, farnesol modulated the morphogenesis of C. albicans through a downregulation of Saps 2, 4, 5, and 6 expressions (Décanis et al, 2011). However, Hultenby et al (2014) reported that treatment of C. albicans with a mixture of propylene glycol, lactic acid and urea resulted in certain ultrastructural changes but without a specific mode of action.…”
Section: Discussionmentioning
confidence: 99%
“…Specific SAP genes were found to be preferentially expressed by Candida hyphal forms [10,15,59]. Because KSL-W downregulated C. albicans growth and transition, this may have occurred through a modulation of the SAP genes.…”
Section: Discussionmentioning
confidence: 99%
“…Because the expression of SAP genes varies depending on the type, phase, and site of infection (52, 62), we analyzed the expression of those genes in yeast cells upon contact with neutrophils, which either performed phagocytosis or exhibited a NETosis mode of action. It should be noted in this regard that SAP gene expression is also regulated during morphological transitions (63,64), which are often caused by physical contact with epithelial cells (65) or plasma proteins (60). The results confirm our supposition that a set of proteases including SAP2, SAP3, and SAP9 is induced in response to these two neutrophil actions.…”
Section: Figmentioning
confidence: 99%